Nitrogen Isotopes of Sinking Particles Reveal the Seasonal Transition of the Nitrogen Source for Phytoplankton. Issue 17 (12th September 2022) - Yoshikawa, Chisato; Ogawa, Nanako O.; Chikaraishi, Yoshito; Makabe, Akiko; Matsui, Yohei; Sasai, Yoshikazu; Wakita, Masahide; Honda, Makio C.; Mino, Yoshihisa; Aita, Maki N.; Fujiki, Tetsuichi; Nunoura, Takuro; et al.
Abstract: In the high‐productivity subarctic ocean, phytoplankton growth is assumed to rely mainly on nitrate, based on snapshot observations conducted in spring or summer. However, the year‐round utilization of nitrate and ammonium by phytoplankton remains unexplored. Here, we show the seasonal transition of the dominant nitrogen source for phytoplankton by using the nitrogen isotopic composition (δ 15 N) of nitrate, ammonium, and sinking particles in the northwestern North Pacific. To decouple the combined effects of nitrogen sources for phytoplankton and subsequent trophic transfers in δ 15 N of sinking particles, we used compound‐specific δ 15 N analysis of amino acids (δ 15 NAA ) in sinking particles. The seasonal change in δ 15 NAA revealed that most of the seasonal variation in δ 15 N of sinking particles arose from changes in the availability of nitrogenous nutrients in the euphotic layer. The δ 15 N of sinking particles suggested that the dominant nitrogen source for phytoplankton switches from nitrate to ammonium in autumn. Plain Language Summary: Exploring the year‐round utilization of nitrate and ammonium by phytoplankton is essential for understanding marine productivity. The nitrogen isotope ratio of sinking particles has long been used for reconstructing the availability of nitrogenous nutrients in the overlying surface water. However, the nitrogen isotope signal of sinking particles represents the combined effects of nitrogen sources for phytoplankton and subsequent trophic transfers, such as zooplankton grazing on phytoplankton and bacterial deamination of organic matter. This study shows the seasonal transition of the dominant nitrogen source for phytoplankton in the northwestern North Pacific by using compound‐specific nitrogen isotope analysis of amino acids in sinking particles that can deconvolute the effect of trophic alterations on bulk nitrogen isotope signals. The compound‐specific nitrogen isotope analysis of amino acids revealed that most of the seasonal variation in the bulk nitrogen isotope signal of sinking particles arises from changes in the availability of nitrogenous nutrients. The seasonal patterns of the bulk nitrogen isotope ratio demonstrated that the dominant nitrogen source for phytoplankton switches from nitrate to ammonium in autumn. Our findings highlight the importance of ammonium as a major nitrogen source for phytoplankton in the high‐productivity subarctic ocean. Key Points: Nitrogen isotope analysis of amino acids in sinking particles can deconvolute the effect of trophic alterations on bulk nitrogen isotope signals Seasonal variation in bulk nitrogen isotope ratios of sinking particles mainly arises from changes in the availability of nitrogenous nutrients Dominant nitrogen source for phytoplankton switches from nitrate to ammonium in autumn in the northwestern North Pacific